2017
DOI: 10.4014/jmb.1607.07064
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Detoxification by Aspergillus oryzae from Meju, a Traditional Korean Fermented Soybean Starter

Abstract: Aflatoxins are classified as Group 1 (carcinogenic to humans) by the International Agency for Research on Cancer. In this study, a total of 134 fungal strains were isolated from 65 meju samples, and two fungal isolates were selected as potential aflatoxin B (AFB)-biodetoxification fungi. These fungi were identified as MAO103 and MAO104 by sequencing the beta-tubulin gene. The two strains were able to degrade more than 90% of AFB (initial concentration: 40 μg/l) in a culture broth in 14 days. The mutagenic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Aflatoxin are mycotoxins and are harmful for both humans and animals due to their mutagenic, carcinogenic, immunosuppressive, hepatotoxic and genotoxic are the reported strains for aflatoxins include A. flavus, A. parasiticus, A. nominus, A. tamarii and A. pseudotamarii [50]. Studies also revealed the sequence similarity of A. flavus with the A. oryzae but A. oryzae is safe and does not produce any aflatoxins and therefore supplemented in food and feed [51].…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxin are mycotoxins and are harmful for both humans and animals due to their mutagenic, carcinogenic, immunosuppressive, hepatotoxic and genotoxic are the reported strains for aflatoxins include A. flavus, A. parasiticus, A. nominus, A. tamarii and A. pseudotamarii [50]. Studies also revealed the sequence similarity of A. flavus with the A. oryzae but A. oryzae is safe and does not produce any aflatoxins and therefore supplemented in food and feed [51].…”
Section: Discussionmentioning
confidence: 99%
“…Two Aspergillus strains ( Aspergillus oryzae MAO103, A. oryzae MAO104) isolated from Meju can effectively degrade AB1 by up to 90% in two weeks and also suppress the growth of AB1 producing Aspergillus flavus . The results suggest that A. oryzae MAO103 and A. oryzae MAO104 strains can be used in various food industries to control the AB1 level [70].…”
Section: Prevention Measuresmentioning
confidence: 99%
“…Furthermore, the authors demonstrated the efficacy of this approach in peanut and sunflower seeds. Weaver et al used [129]. Villers [130] detailed field experience governing the exponential growth of aflatoxins during prolonged postharvest storage of grains in tropical countries.…”
Section: Novel Approaches For Tackling Aflatoxin Contaminationmentioning
confidence: 99%